A compressed sensing approach for antenna array calibration - Akinwale Oluwaseyi Fadamiro; Fujiang Lin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
This paper presented a compressive sensing (CS) calibration technique that simultaneously measures all the element excitations of a 2×2 active phased antenna array (APAA) instantaneously. The power patterns of the rectangular 2×2 APAA element are synchronized to orthogonally cross multiplicative sub-array system applying compressive sensing in achieving an array thinning along two 1-D sub-arrays for a fixed steered beam radiation. The far field radiation pattern direction of the 2×2 APAA is examined considering the mutual effect, complex excitation of the amplitude and phase of the antenna elements placed on the x and y axes. The unwanted array excitation with errors are calibrated using minimization vector as a standard basic pursuit problem in compressive sensing technique for the 2×2 APAA calibration. The elements amplitude and phase shift variation are compared with reference state 0 in order to evaluate the faulty error array elements. The performance evaluation of this proposed technique is measured and demonstrated to validate the effectiveness of the proposed antenna calibration technique.